(untitled) (International Journal of Engineering and Computer Science, 2014)
Vehicular ad-hoc network (VANET) has created their importance in network area, because of their special characteristics. The important characteristics of VANET are high mobility, self organization, no restrictions on network size all these characteristics made VANET environment a challenging for developing efficient routing protocols. For the better performance in network VANET require a special support, which made a network fast, secure and efficient, the best solution to that is an Opportunistic routing. This paper build a trusted opportunistic forwarding model in VANET, it incorporates trust mechanism into OR and to enhance the security of routing and protect the network from malicious attack. This paper focuses on the ratio of throughput, delay and security must be good more than existing protocols. In this paper, TMCOR and TOMCOM routing protocol are proposed, which are trusted minimum cost opportunistic unicast routing protocol and multicast routing protocol.